Effects of incorporating large quantities of copper tailings with various particle sizes on the strength and pore structure of cement-based materials. (25th April 2022) - Chen, Sung-Ching; Gao, Meng-Yao; Lin, Wei-Ting; Liang, Jiong-Feng; Li, Dong-Wei
Graphical abstract: Highlights: An environment-friendly fine aggregate for the reuse of copper tailings was developed. Use of specific grades to improve the reusability and specimen strength. Effects of finer particles improved the strength of the copper tailings specimens. Specific grades of fine-grained tailings provided hydration to fill the pore space. Abstract: Although it is estimated that approximately 300 million tons of copper tailing is produced in China annually, only about 8.2% of this byproduct is reused. Therefore, to promote natural material sustainability, and value-added utilization of copper tailings in China, tailings from Hubei (HT) and Jiangxi (JT) were explored as replacement materials for the fine natural aggregate. The water/cement ratio was fixed at 0.50, and various proportions of fine aggregate were replaced (0%, 30%, 50%, 70%, and 100%). The size distribution of the tailings particles was as follows: HT (1.18 to 0.15 mm) and JT (0.60 to 0.15 mm). This study was made to match the size distribution of the tailings with that of the fine aggregate it replaced. The mechanical properties and pore structure were assessed using the methylene blue test, flexural tensile strength test, compressive strength test, absorption test, fluidity test, mercury intrusion porosimetry (MIP) test, and scanning electron microscopy (SEM). The control group (without tailings) presented the highest flexural strength but the lowest compressive strength. The experiment group achieved the highest flexural and compressive strength under 50% HT content or 70% JT content. Overall, MIP results show that inclusions in tailings tend to reduce "harmless pores" (pores < 20 nm). SEM observations at 7 days revealed that unreacted tailings particles filled the macropores between fine aggregate and paste. Observations at 28 days revealed fewer unreacted tailings particles. The finer tailings particles reacted with calcium hydroxide in cement to form hydrated calcium silicate gel and fill pores, thereby enhancing the strength of cement mortar.